2010
DOI: 10.1038/eye.2010.83
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of agreement between intraocular pressure measurements using Goldmann applanation tonometry and Goldmann correlated intraocular pressure by Reichert's ocular response analyser

Abstract: Purpose To compare agreement of intraocular pressure (IOP) measurements using Goldmann applanation tonometry (GAT) and Goldmann correlated intraocular pressure generated (IOPg) by the Reichert ocular response analyser (ORA). Methods Consecutive patients presenting for glaucoma evaluation underwent ORA assessment followed by examination including GAT. For each ORA assessment, measurements were taken until a waveform score (WS) of 6.5 was obtained or until five measurements were obtained per eye. The relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 38 publications
(43 reference statements)
3
27
0
Order By: Relevance
“…Another limitation is that we measured IOP using the Ocular Response Analyzer in the majority of cases rather than by GAT, which is the gold standard technique for measuring IOP. Previous studies have shown there is good agreement between GAT and Ocular Response Analyzer Goldmann-correlated IOP 35 and repeatability of Ocular Response Analyzer IOP measurements is comparable to that of GAT. 36 Therefore, we believe this is unlikely to be of clinical significance.…”
Section: Discussionsupporting
confidence: 61%
“…Another limitation is that we measured IOP using the Ocular Response Analyzer in the majority of cases rather than by GAT, which is the gold standard technique for measuring IOP. Previous studies have shown there is good agreement between GAT and Ocular Response Analyzer Goldmann-correlated IOP 35 and repeatability of Ocular Response Analyzer IOP measurements is comparable to that of GAT. 36 Therefore, we believe this is unlikely to be of clinical significance.…”
Section: Discussionsupporting
confidence: 61%
“…In the present study, IOP was measured using the ORA, despite the accepted gold standard technique for measuring IOP being Goldmann applanation tonometry (GAT). However, there is good agreement between GAT and ORA Goldmann-correlated IOP,23 and the repeatability of ORA IOP measurements is comparable to that of GAT 24. Relative to posterior segment OCT imaging, anterior segment OCT imaging and analysis is still in its infancy, and its features differ markedly between software versions and manufacturers.…”
Section: Discussionmentioning
confidence: 96%
“…In addition to the impact of these parameters on the accuracy of Goldmann applanation tonometry (GAT) [5][6][7][8][9][10], it has been shown that these parameters are significantly reduced in glaucoma patients and appear to be a risk factor for glaucoma progression [11][12][13].…”
Section: Introductionmentioning
confidence: 99%